Coaseian biodiversity conservation. Who benefits? - Thomas Eichner; Rüdiger Pethig (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We analyze strategies to conserve worldwide biodiversity assuming that biodiversity and ecosystem services are positively correlated with that share of land that is effectively protected by land-use restrictions against the deterioration of ecosystems (land-use approach). The willingness-to-pay for biodiversity conservation is positive in developed countries (North), but zero in developing countries (South). The strategies of biodiversity conservation are cooperation among the North (Regime 2) and financial support of biodiversity conservation from North to South modeled as an international market for biodiversity conservation (Regime 3). We investigate the impact on biodiversity conservation and welfare when the world economy moves from business as usual (BAU, Regime 1) to the stand-alone Regimes 2 and 3 and to the combination of the Regimes 2 and 3, called Regime 4. Regime 4 turns out to be the Coaseian socially optimal solution to biodiversity conservation. In a parametric version of the model, we derive a number of unexpected results. The move from BAU to Regime 2 may reduce biodiversity conservation and welfare in North and South. Regime 3 fares better, but it hardly improves welfare and the conservation of biodiversity in our simulations. Although Regime 4 is socially optimal, its distributional effects may be undesirable, because the North or the South are worse off in Regime 4 than in BAU for some subsets of parameters.
Keywords: Q15; Q57; Q58; 330